Harmonization of Electronic Signature Regulations in Notarial Practice: A Comparative Analysis of The Notary Law and The Electronic Information and Transactions Law - Ninda Tria Permatasari; Udin Narsudin; Dewy Nelly Yanthy (Magister Kenotariatan Universitas Pasundan, 2025)
The rapid development of digital technology has heightened the urgency of adopting electronic signatures in legal transactions, including notarial practice. However, regulatory disharmony between the Notary Law (UUJN) and the Electronic Information and Transactions Law (ITE Law) creates legal uncertainty in its implementation. The UUJN requires physical presence and manual signatures for authentic deeds, while the ITE Law recognizes the legal validity of electronic signatures. This study aims to analyse the regulatory disharmony between these two laws and to formulate a harmonisation framework for the implementation of electronic signatures in notarial practice. This research employs a normative juridical method, drawing on statutory and conceptual approaches. Data were collected through library research on primary and secondary legal materials and analysed qualitatively using the Miles and Huberman technique. The findings reveal three main aspects of disharmony: physical presence requirements, signature form specifications, and document authentication procedures. The study concludes that regulatory harmonization can be achieved through amendments to the UUJN that accommodate certified electronic signatures for official reports (akta relaas), while maintaining physical presence requirements for party deeds (akta partij). The harmonization framework requires electronic certification standards supervised by the National Cyber and Encryption Agency (BSSN), technical guidelines from the Indonesian Notary Association, and public education regarding the validity of digital documents. This research contributes to the legal discourse on modernizing notarial practice in Indonesia while maintaining legal certainty and document authenticity.